Nahe Biti Boot Sebagai Model Rekonsiliasi Masyarakat Berkonflik Di Timor Leste (Evaluasi Kritis Terhadap Proses Rekonsiliasi Komunitas CAVR) - , Flavianus D.Melsasail, Ahmad Hanafi Rais, SIP,MPP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
of This research aims to provide an overview that the nahe biti boot should be considered as the main choice conflict resolution system in Timor Leste. A similar culture and their belief to âadatâ are the main pillars for nahe biti boot to be used to solve the conflict. Nahe biti boot is a traditional court model of Timor Leste. have This research was motivated by a sentiment and suspicious among pro autonomy and pro independent, whereas reconciliation efforts to fix their relations through the Community Reconciliation Process (CRP) been carried out. Started from critics to CRP and the need to fix the relations between conflicted people, nahe biti boot can be used as the alternative way to solve conflicts and creates a good relation among them. on This research used qualitative research methods by using the literature study to collect data and the implementation rival as the analysis technique. Some theories are being used to analyze in this paper, including the theory of reconciliation, peace and social capital concept which aimed to guide and strengthen the main argument of this paper. The result of this research is that any form of reconciliation techniques has its own advantages and disadvantages, so the decision makers need to understand and evaluate that the reconciliation technique are need to be adjusted to the conflict environment, as well as the local culture. The understanding of the local culture is very important because it is the main key of successful rec ciliation process.